2004
DOI: 10.1021/ie049815x
|View full text |Cite
|
Sign up to set email alerts
|

Monodisperse Nanoparticle Synthesis by an Atmospheric Pressure Plasma Process:  An Example of a Visible Light Photocatalyst

Abstract: An atmospheric pressure plasma-enhanced nanoparticle synthesis (APPENS) process was proposed to produce a titania-based visible light photocatalyst. The titanium tetraisopropoxide (TTIP) precursor was vaporized with a N2 carrier gas and entered a nonthermal AC plasma system. The N2 gas was dissociated into N atoms by the plasma energy, and then they were doped into the precursor vapors. The produced TiO2 - x N x nanoparticles were highly uniform and adjustable in size. The titania-based particle sizes ranged… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2005
2005
2014
2014

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 22 publications
0
11
0
Order By: Relevance
“…Using such configurations, simple atmospheric plasma systems using nitrogen, argon or helium as a carrier gas can produce high particle concentrations without requiring a complicated vacuum system. Particles have been successfully produced from ferrocene, acetylene and hexamethyldisiloxane (Vons et al 2006), and from titaniumisopropoxide for the production of titania particles (Bai et al 2004;). Furthermore, this type of plasma can also be used for gas-phase particle coating, both for particles from another DBD plasma or particles produced using other methods (e.g.…”
Section: Plasma Synthesismentioning
confidence: 99%
“…Using such configurations, simple atmospheric plasma systems using nitrogen, argon or helium as a carrier gas can produce high particle concentrations without requiring a complicated vacuum system. Particles have been successfully produced from ferrocene, acetylene and hexamethyldisiloxane (Vons et al 2006), and from titaniumisopropoxide for the production of titania particles (Bai et al 2004;). Furthermore, this type of plasma can also be used for gas-phase particle coating, both for particles from another DBD plasma or particles produced using other methods (e.g.…”
Section: Plasma Synthesismentioning
confidence: 99%
“…It can be seen that the XRD pattern of TiO 2 clearly indicates characteristic peaks of the anatase form of TiO 2 crystals. 30 The major peaks that appeared in the 2 range between 22°and 25°and 7°and 9°correspond to the specific peaks of H-ZSM-5 zeolite. 31 As the content of H-ZSM-5 zeolite is increased in the TiO 2 /zeolite composites, the gradual increase in the intensity of the zeolite peaks and the decrease in the intensity of the TiO 2 peaks are clearly observed.…”
Section: Resultsmentioning
confidence: 91%
“…It can be noticed, however, that H 2 O is a reactant that ensures direct hydrolysis of TTIP without necessary implementation of plasma. Although definite differences between the particles deposited with and without plasma were observed, certain ambiguity remained about CVD/PECVD interrelation in this process.…”
Section: Introductionmentioning
confidence: 96%
“…However, only the possibility to fabricate TiO 2 coatings by this method was demonstrated. A more detailed research was presented by Liu and Lai, Klenko and Pichal, and Bai with co‐workers who prepared crystalline TiO 2 nanoparticles by atmospheric pressure plasma in the TTIP/H 2 O + N 2 /O 2 /Ar mixtures with subsequent annealing. It was shown that different types of N‐doping of TiO 2 were realized depending on the working gas and/or annealing gas composition.…”
Section: Introductionmentioning
confidence: 99%